Ionized gas outflows and global kinematics of low-z luminous star-forming galaxies. Issue Volume 10:Issue S309(2014) (9th February 2015) - Arribas, S.; Colina, L.; Bellocchi, E.; Maiolino, R.; Villar-Martín, M.
Abstract: We have studied the kinematic properties of the ionized gas outflows and ambient interstellar medium (ISM) in a large and representative sample of local U/LIRGs (58 systems, 75 galaxies) at galactic and sub-galactic (i.e., star-forming clumps) scales, thanks to integral field spectroscopy (IFS)-based high signal-to-noise integrated spectra. The main results have been recently presented in Arribas et al. (2014 ), and are briefly summarized here.